Effectiveness of various surgical methods in treatment of Hirschsprung’s disease in children - Lukač Marija; Sinđić-Antunović Sanja; Vujović Dragana; Petronić Ivana; Nikolić Dejan; Radlović Vladimir; Krstajić Tamara; Krstić Zoran (Vojnosanitetski Pregled)
Background/Aim. Hirschsprung’s disease is the most common identifiable developmental disorder of the enteric nervous system, characterized by a failure of its formation in a variable segment of distal bowel. Currently available surgical therapies for Hirschsprung’s disease, although lifesaving, are associated with numerous complications. The aim of our study was to evaluate the effectiveness of different surgical methods and the incidence of serious complications after radical surgery of rectosigmoid Hirschsprung’s disease. Methods. A retrospective analysis, from June 1997 until May 2012 was carried out on 84 patients operated for Hirschsprung’s disease of rectosigmoid colon. Transanal endorectal pull-through was performed in 30 (35.7%) patients (group I), while 54 (64.3%) patients were operated by other (Soave, Duhamel or Swenson) procedures (group II). The age at operation, the incidence and severity of postoperative complications, the need for previous colostomy and the number of reoperations are countered in order to evaluate the efficacy of surgical procedures. Results. In the group I, the mean age at operation was 9.41 ± 6.37 months and in the group II the mean age at operation was 16.8 ± 13.9 months which was significantly higher (p < 0.01). In the group I there were only 3 (10%) patients with complications, one (3%) of them was prone to only one redo procedure (1.00 ± 0.00) and there was no need for previous colostomy in all patients (100%). In the group II there were 16 (30%) patients with significantly frequent complications (p < 0.05), about 2 reoperations on the average (1.94 ± 1.84) in 4 of them (25%) and 22 (41%) redo procedures, which was, in total, significantly higher than in the group I (p < 0.01). Only Soave’s procedure was performed without previous colostomy in 20 (37%) patients. Conclusion. Transanal endorectal pull-through in surgical treatment of patients with Hirschsprung’s disease is more effective than other procedures concerning earlier onset, low incidence and less severe complications, which would require further operations, and no scars.